Analysis of the Arabic Language Textbook for Junior High School from the Perspective of the Education, Standards, Curiculum, and Assesment Agency (BSKAP) - Amalia, Nabila Nailil; M. Abdul Hamid; Zakiyah Arifa; Asbarin (IAIN Madura, 2024)
Many textbooks available in the market require educators to be selective when choosing and using them as sources of knowledge to support learning. A high-quality textbook should align with the developmental and growth stages of students to achieve national educational goals. This study aims to evaluate and develop Arabic language textbooks based on BSKAP qualifications. The research employs a qualitative-evaluative approach, specifically a library research study with content analysis. For data analysis, Krippendorf's model is used, and the validity of the data is ensured by cross-checking the findings. The study's results highlight four aspects of textbook feasibility established by BSKAP: content/material feasibility, presentation feasibility, language feasibility, and design/graphic feasibility. Some indicators within each aspect require revisions, additional materials, and innovations from the authors of the Arabic textbooks under KMA 183 and the Arabic language educators who are implementing the independent curriculum.